Long-Term Outcomes in Severe Community-Acquired Pneumonia - Carella, Francesco; Aliberti, Stefano; Stainer, Anna; Voza, Antonio; Blasi, Francesco (Seminars in Respiratory and Critical Care Medicine, 2024)
Community-acquired pneumonia (CAP) is globally one of the major causes of hospitalization and mortality. Severe CAP (sCAP) presents great challenges and need a comprehensive understanding of its long-term outcomes. Cardiovascular events and neurological impairment, due to persistent inflammation and hypoxemia, contribute to long-term outcomes in CAP, including mortality. Very few data are available in the specific population of sCAP. Multiple studies have reported variable 1-year mortality rates for patients with CAP up to 40.7%, with a clear influence by age, comorbidities, and disease severity. In terms of treatment, the potential protective role of macrolides in reducing mortality emphasizes the importance of appropriate empiric antibiotic therapy. This narrative review explores the growing interest in the literature focusing on the long-term implications of sCAP. Improved understanding of long-term outcomes in sCAP can facilitate targeted interventions and enhance posthospitalization care protocols.
Keywords: severe community-acquired pneumonia; long-term outcomes; long-term mortality; narrative review